Geology, Alteration, and Mineralization of the Kay Tanda Epithermal Gold Deposit, Lobo, Batangas, Philippines. Issue 4 (20th May 2019) - Frias, Sofia Marah P.; Imai, Akira; Takahashi, Ryohei; Balangue‐Tarriela, Ma. Ines Rosana; Arcilla, Carlo; Blamey, Nigel
Abstract: The Kay Tanda epithermal Au deposit in Lobo, Batangas is one of the Au deposits situated in the Batangas Mineral District in southern Luzon, Philippines. This study aims to document the geological, alteration, and mineralization characteristics and to determine the age of the mineralization, the mechanism of ore deposition, and the hydrothermal fluid characteristics of the Kay Tanda deposit. The geology of Kay Tanda consists of (i) the Talahib Volcanic Sequence, a Middle Miocene dacitic to andesitic volcaniclastic sequence that served as the host rock of the mineralization; (ii) the Balibago Diorite Complex, a cogenetic intrusive complex intruding the Talahib Volcanic Sequence; (iii) the Calatagan Formation, a Late Miocene to Early Pliocene volcanosedimentary formation unconformably overlying the Talahib Volcanic Sequence; (iv) the Dacite Porphyry Intrusives, which intruded the older lithological units; and (v) the Balibago Andesite, a Pliocene postmineralization volcaniclastic unit. K‐Ar dating on illite collected from the alteration haloes around quartz veins demonstrated that the age of mineralization is around 5.9 ± 0.2 to 5.5 ± 0.2 Ma (Late Miocene). Two main styles of mineralization are identified in Kay Tanda. The first style is an early‐stage extensive epithermal mineralization characterized by stratabound Au‐Ag‐bearing quartz stockworks hosted at the shallower levels of the Talahib Volcanic Sequence. The second style is a late‐stage base metal (Zn, Pb, and Cu) epithermal mineralization with local bonanza‐grade Au mineralization hosted in veins and hydrothermal breccias that are intersected at deeper levels of the Talahib Volcanic Sequence and at the shallower levels of the Balibago Intrusive Complex. Paragenetic studies on the mineralization in Kay Tanda defined six stages of mineralization; the first two belong to the first mineralization style, while the last four belong to the second mineralization style. Stage 1 is composed of quartz ± pyrophyllite ± dickite/kaolinite ± diaspore alteration, which is cut by quartz veins. Stage 2 is composed of Au‐Ag‐bearing quartz stockworks associated with pervasive illite ± quartz ± smectite ± kaolinite alteration. Stage 3 is composed of carbonate veins with minor base metal sulfides. Stage 4 is composed of quartz ± adularia ± calcite veins and hydrothermal breccias, hosting the main base metal and bonanza‐grade Au mineralization, and is associated with chlorite‐illite‐quartz alteration. Stage 5 is composed of epidote‐carbonate veins associated with epidote‐calcite‐chlorite alteration. Stage 6 is composed of anhydrite‐gypsum veins with minor base metal mineralization. The alteration assemblage of the deposit evolved from an acidic mineral assemblage caused by the condensation of magmatic volatiles from the Balibago Intrusive Complex into the groundwater to a slightly acidic mineral assemblage caused by the interaction of the host rocks and the circulating hydrothermal waters being heated up by the Dacite Porphyry Intrusives to a near‐neutral pH toward the later parts of the mineralization. Fluid inclusion microthermometry indicates that the temperature of the system started to increase during Stage 1 (T = 220–250°C) and remained at high temperatures (T = 250–290°C) toward Stage 6 due to the continuous intrusion of Dacite Porphyry Intrusives at depth. Salinity slightly decreased toward the later stages due to the contribution of more meteoric waters into the hydrothermal system. Boiling is considered the main mechanism of ore deposition based on the occurrence of rhombic adularia, the heterogeneous trapping of fluid inclusions of variable liquid–vapor ratios, the distribution of homogenization temperatures, and the gas ratios obtained from the quantitative fluid inclusion gas analysis of quartz. Ore mineral assemblage and sulfur fugacity determined from the FeS content of sphalerite at temperatures estimated by fluid inclusion microthermometry indicate that the base metal mineralization at Kay Tanda evolved from a high sulfidation to an intermediate sulfidation condition. Abstract : The Kay Tanda epithermal Au deposit in Lobo, Batangas is one of the Au deposits situated in the Batangas Mineral District in southern Luzon, Philippines. It was formed in an evolving hydrothermal system that is composed of two mineralization styles: (i) an early‐stage Au‐Ag mineralization hosted in quartz stockworks in the shallower levels of the deposit and (ii) a late‐stage Zn‐Pb‐Cu‐Au mineralization hosted in quartz ± adularia ± calcite veins, anhydrite‐gypsum veins, and hydrothermal breccias in the deeper levels of the deposit. Boiling is the main mechanism of ore mineralization, which is supported by much evidence, such as the presence of rhombic adularia in veins, coexistence of fluid inclusions of variable liquid–vapor ratios, homogenization temperature histograms showing skewness to higher temperatures, and boiling slopes in gas analysis plots.